Money supply and interest rate in recent macroeconomic conceptions. A rejoinder - GAMBINO, A. (PSL Quarterly Review, 2014)
In two studies from recent years Professor Amadeo Gambino reopened the discussion of the problem of the determinants of the volume of bank deposits. The conclusions reached in these studies diverged from the well-known Keynesian proposition according to which the volume of deposits is determined almost exclusively by the monetary authorities. Moreover, he specifically criticised Professor Schneider for asserting the general validity of that proposition. In the present rejoinder, Gambino responds to Schneider’s Comment, setting out the points of agreement and disagreement, and summarising the most signifiant results of his own studies. JEL: E51, E52, E58